2011
DOI: 10.1126/science.1198315
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Reactivity of an Iron(V) Nitride

Abstract: Despite being implicated as important intermediates, iron(V) compounds have proven very challenging to isolate and characterize. Here, we report the preparation of the iron(V) nitrido complex, [PhB((t)BuIm)(3)Fe(V)≡N]BAr(F24) (PhB((t)BuIm)(3)(-) = phenyltris(3-tert-butylimidazol-2-ylidene)borato, BAr(F24) = B(3,5-(CF(3))(2)C(6)H(3))(4)(-)), by one electron oxidation of the iron(IV) nitrido precursor. Single-crystal x-ray diffraction of the iron(V) complex reveals a four-coordinate metal ion with a terminal nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
272
0
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 328 publications
(297 citation statements)
references
References 22 publications
15
272
0
10
Order By: Relevance
“…pentavalent Fe V ≡N complex [(PhB( t BuIm) 3 )Fe V (N)] + , which is the first example of an Fe V ≡N that could be isolated and thoroughly characterized in solution and in solid state 92 . An X-ray diffraction study revealed overall similar bond metrics to its tetravalent precursor, with the most remarkable feature being the very short Fe-N bond distance of 1.502 Å in crystals of [(PhB( t BuIm) 3 93 Table 1), showing localized valencies in the asymmetric mixed-valent complex 95 .…”
Section: Iron-nitrido Model Complexesmentioning
confidence: 99%
“…pentavalent Fe V ≡N complex [(PhB( t BuIm) 3 )Fe V (N)] + , which is the first example of an Fe V ≡N that could be isolated and thoroughly characterized in solution and in solid state 92 . An X-ray diffraction study revealed overall similar bond metrics to its tetravalent precursor, with the most remarkable feature being the very short Fe-N bond distance of 1.502 Å in crystals of [(PhB( t BuIm) 3 93 Table 1), showing localized valencies in the asymmetric mixed-valent complex 95 .…”
Section: Iron-nitrido Model Complexesmentioning
confidence: 99%
“…[1,11,13] Figure 4 shows the example of the scheme in which different high-valent species have been demonstrated. Details of the scheme has been given elsewhere.…”
Section: Iron-nitrido Complexesmentioning
confidence: 99%
“…[6,10] In addition to iron oxo species, high-valent ironnitrido complexes have also been suggested to play significant role in nitrogenase enzyme reactions and industrial Haber-Bosch process. [11][12][13] Figure 2 depicts the postulated intermediates with iron-nitrogen multiple bonds. [1] At the single iron site, reduction of nitrogen may occur.…”
Section: Introductionmentioning
confidence: 99%
“…16−18 A tris(carbine)amine-iron(IV)-nitride was recently employed as an electrochemical precursor for a complementary iron(V) species that was stable enough for its electronic and molecular structure to be examined by crystallography and various types of spectroscopy. 19,20 Quite in contrast, iron nitrides with a fourfold symmetrical coordination geometry at the metal center are highly unstable under ambient conditions. The existence of square pyramidal and pseudo-octahedral nitrido-iron species under cryogenic conditions has been deduced from early resonance Raman spectra 21 or from a detailed spectral analysis of their decomposition products.…”
Section: ■ Introductionmentioning
confidence: 99%